Spatial Distribution Pattern of Plants with Potential to Regulate Water Balance in the Babak Watershed Upstream Area - Prasetyo, Andrie Ridzki; Valentino, Niechi; Setiawan, Budhy; Shabrina, Hasyyati; Chaerani, Nurul; Syahruanda, Eggi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Watershed degradation poses a serious threat to water availability, ecosystem sustainability, and human well-being. This study aims to identify and analyze the spatial distribution patterns of three key water-regulating plant species Pterospermum javanicum, Ficus spp., and Dendrocnidae decumana in the upstream area of the Babak Watershed, Lombok, Indonesia. Field data were collected through exploratory surveys and analyzed using the Average Nearest Neighbor (ANN) method in ArcGIS 10.8. The results reveal distinct spatial patterns: D. decumana exhibits a random distribution (R = 0.925), while Ficus spp. (R = 0.667) and P. javanicum (R = 0.698) show clustered patterns. These patterns reflect ecological adaptations such as tolerance to environmental heterogeneity or vegetative reproduction strategies. Despite differences, all three species significantly contribute to watershed hydrology by enhancing infiltration, reducing surface runoff, and stabilizing soil. Spatial analysis of vegetation distribution provides essential insights for data-driven watershed management and supports targeted conservation strategies in ecologically sensitive upstream zones.